Dari Modernisme Islam ke Islamisme: Transformasi Ideologi dan Gerakan Islam di Aceh - Alkaf, M. Alkaf; Che Noh , Noorsafuan; Hakam , Saiful; Said , Muhammad; Fahmi, Khairul (Program Pascasarjana IAIN Langsa, 2025)
This study examines how Islamic modernism in Aceh evolved into Islamism, based on evidence from historical records. The author argues that Islamic modernism played a key role in shaping the rise of Islamism in Aceh. To support this, the study breaks the development into three key periods. The first period focuses on the spread of Islamic modernist ideas through the madrasa network. The second period explores how these ideas interacted with the growing sense of Indonesian nationalism. The third period examines how Islamist ideas became more established, particularly with the introduction of local democracy after the peace agreement that ended the conflict. This study employs a qualitative methodology with a historical approach, with data collected through literature review and archival document analysis. The study concludes that Islamic modernism was important in forming Islamist ideology in Aceh. The study concludes that Islamic modernism was important in forming Islamist ideology in Aceh. Unlike other studies that link Islamic modernism with support for democracy, this research shows that in Aceh, the shift from Islamic modernism to Islamism has led to a more skeptical attitude toward modern concepts like human rights and democracy. This study offers a nuanced perspective on the ideological trajectory of Islamic thought in Aceh by challenging the dominant narrative that Islamic modernism is inherently aligned with democratic values. Through a periodized analysis and a focus on Aceh’s unique political history, the study enriches our understanding of the complex relationship between religion, nationalism, and democratization in Muslim-majority regions.